Federalism in Russia After 1991 - Srivastava, Rachit (International studies (New Delhi), 2023)
This article examines the federalization process and the spread of federalism in Russia after 1991. The Russian federal system has undergone several changes since the collapse of the Soviet Union. It arose as a result of several contracts signed between the federal government and the subjects. The federal structure of Russia is asymmetric and characterized by conflicts due to the system of division of power between the federal government and the subjects. The creation of an institutional mechanism was done to facilitate the application of the federal principles effectively. The President’s full control over political affairs, foreign policy and the economy can harm the successful development of the federal state in Russia.